Effect of Problem-Based Learning Approach Assisted by GEO-KODE on Understanding the Mathematical Concepts of Composition and Decomposition of Plane Shapes - Gina Dwi Arista; Isrok'atun Isrok'atun; Ani Nur Aeni (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Abstract Students’ limited understanding of mathematical concepts may hinder their ability to solve problems requiring analysis of relationships among concepts. This study examined the effectiveness of Problem-Based Learning (PBL) supported by GEO-KODE (Geometry-Composition Decomposition), an interactive learning medium designed to help students visualize the composition and decomposition of plane figures. A quantitative quasi-experimental method with a nonequivalent control group design was employed. The participants were 61 fourth-grade students selected through purposive sampling. The experimental group consisted of 31 students from Cijambe II Public Elementary School, while the control group included 30 students from Sukamulya Public Elementary School. Data were collected using a mathematical concept understanding test consisting of 15 valid items with high reliability. Data analysis included tests of normality, differences in mean scores, and normalized gain (N-Gain). The experimental group’s mean score increased from 31.55 on the pretest to 74.97 on the posttest, whereas the control group’s mean score increased from 38.83 to 51.77. A significant difference in posttest performance was found between the two groups (p < .001). The N-Gain analysis also showed a significant difference in improvement between the experimental and control groups (p < .001). These findings indicate that students who learned through PBL supported by GEO-KODE demonstrated greater improvement in mathematical concept understanding than those who received conventional instruction. The results suggest that integrating problem-based activities with interactive visual media can support fourth-grade students in understanding the composition and decomposition of plane figures, particularly by making relationships among component shapes more explicit during classroom problem solving.